Pemahaman Epistemologi Siswa Di Madrasah Ibtidaiyah Al-Hasan Kota Bandung - Fauji, Ikang; Nugraha, Mulyawan Safwandy (Peneliti.net, 2025)
This study is related to the importance of understanding epistemology among students at Madrasah Ibtidaiyah Al-Hasan in Bandung, considering the increasingly complex and diverse developments in education. In the context of globalization and digitalization, a good understanding of epistemology will help students assess, choose, and effectively utilize various sources of knowledge. The purpose of this research is to identify how students utilize available knowledge sources and how this contributes to the development of their epistemological understanding. This study also aims to understand the constraints and challenges faced in accessing knowledge sources. The method applied in this study is a qualitative approach with techniques such as interviews, field observations, and document analysis. The information involved in this study includes students and teachers who provide diverse perspectives on the use of knowledge sources. The results show that students have varying levels of understanding about epistemology. Most students tend to rely on traditional knowledge sources, such as textbooks and teachings from teachers, while a small number have begun to explore digital and non-traditional knowledge sources, such as the internet and social media. The study also identifies several challenges, including the lack of training for students in critically using digital knowledge sources. The conclusion of this study highlights the need to strengthen epistemology education at the madrasah, providing broader access to diverse knowledge sources, as well as the importance of training teachers to facilitate a deeper understanding of how students access and utilize knowledge. Thus, this research is expected to contribute to the development of more effective curricula and teaching methods in the madrasah environment.